PENGGUNAAN CITRA SATELIT QUICKBIRD UNTUK PENENTUAN PRIORITAS LOKASI PERUMAHAN DI KECAMATAN BANGUNTAPAN KABUPATEN BANTUL - , RESTA GUNAWAN, Sigit Heru Murti B.S., S.Si, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of these research are:1) Assesing the accuracy of Quickbird Imagery to get influenced parameter for housing location priority determination, 2) Determine land suitability based on physical and acessibility parameters, 3) To make housing location priority maps. The methods of research were the combination among visual interpretation, technique, fieldwork, geography data processing and analysis. Interpretation of Quickbird Imagery used as primary data source. Land suitability parameters for housing location priority determination obtained by several method. Landuse, road network, and public facilities location were obtained from Quickbird Imagery interpretation and help by RBI maps. Slope obtained from RBI maps. Flood vulnerability obtained from secondary data combined by fieldwork. Water supply and electricity networks obtained from secondary data. Analysis wich was used to determine housing location, used quantitative approach, and it is done by weight factor scoring method. The final result is housing location priority maps. The result show the Quickbird Imagery can be used to get housing location parametes, the mapping accuracy for landuse are 87.71%. The result of housing location priority are